The platformization of science: Lattes Platform at a crossroads? - Tulio Chiarini; Victo José da Silva Neto (Institute for Applied Economic Research (ipea), 2022)
In this Discussion Paper, we focus our analysis on the Lattes Platform - a public initiative developed endogenously in the late 1990s which was very innovative - since it is a representative case of a scientific platform and is a paramount tool for the Brazilian scientific system. Although there are many academic studies published using data provided by the Lattes Platform, we identified a lack of official reports and articles that address Lattes as a digital platform and its adequacy in the context of the platform economy. We propose that the early-stage technology choices made by CNPq and the constant budget cuts for the Lattes Platform's maintenance and technological upgrading have strongly affected the platform's trajectory. As a consequence, the Lattes Platform may be locked-in to a technological trajectory that could lead to the stagnation of its functionalities, putting at risk its indispensable and infrastructural character.
Keywords: O30; O33; O38; 330; Lattes platform; platformization of science; platform infrastructuralization; science policy